Critical evaluation of the Global DOTS Expansion Plan - Donald A Enarson; Nils E Billo (The World Health Organization, 2007)
The development of the DOTS Expansion Plan has been a milestone in tuberculosis (TB) control at the global and national levels. Key challenges that remain are overcoming the weakness of a strategy built on case management, sustaining commitment, competing priorities, the threat of HIV, maintaining high quality of care and preventing drug resistance, building human resource capacity, improving diagnosis and fostering operations research. The ability to address these challenges will determine the success or failure of the Global Plan to Stop TB, 2006-2015.